1997
DOI: 10.1016/s0014-5793(97)00225-1
|View full text |Cite
|
Sign up to set email alerts
|

On the involvement of calpains in the degradation of the tumor suppressor protein p53

Abstract: A crude fraction that contains ubiquitin-protein ligases contains also a proteolytic activity of ~100 kDa that cleaves p53 to several fragments. The protease does not require ATP and is inhibited in the crude extract by an endogenous ~250 kDa inhibitor. The proteinase can be inhibited by chelating the Ca 2+ ions, by specific cysteine proteinase inhibitors and by peptide aldehyde derivatives that inhibit calpains. Purified calpain demonstrates an identical activity that can be inhibited by calpastatin, the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 25 publications
1
52
1
1
Order By: Relevance
“…Thus the ATP-dependent degradation of N-myc, which is thought to be mediated by the proteasome, can be inhibited by immunologic depletion of the E1 ubiquitin-activating enzyme (Ciechanover et al, 1991(Ciechanover et al, , 1994. At the same time, as previously shown for ornithine decarboxylase Rosenberg-Hasson et al, 1989), c-Jun (Jariel-Encontre et al, 1995) and p53 (Gonen et al, 1997), in vitro degradation of N-myc can also proceed via a calpaindependent ubiquitin-independent pathway (Gonen et al, 1997).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Thus the ATP-dependent degradation of N-myc, which is thought to be mediated by the proteasome, can be inhibited by immunologic depletion of the E1 ubiquitin-activating enzyme (Ciechanover et al, 1991(Ciechanover et al, , 1994. At the same time, as previously shown for ornithine decarboxylase Rosenberg-Hasson et al, 1989), c-Jun (Jariel-Encontre et al, 1995) and p53 (Gonen et al, 1997), in vitro degradation of N-myc can also proceed via a calpaindependent ubiquitin-independent pathway (Gonen et al, 1997).…”
Section: Discussionsupporting
confidence: 56%
“…The involvement of an ATP-dependent degradation pathway in vitro in the turnover of N-myc and other nuclear regulatory proteins (c-Myc, c-Fos, E1A and p53) has been demonstrated, however high molecular weight ubiquitin conjugates of N-myc were not observed (Ciechanover et al, 1991). In addition, a recent in vitro study has also implicated calpain in N-myc degradation (Gonen et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of wild type p53 in MCF7 is a positive control for PS-341 activity resistant to ALLN (Figures 2a and 3c). Accumulation of wild type p53, previously shown to be sensitive to calpain as well as proteasome inhibition (Gonen et al, 1997;Kubbutat and Vousden, 1997;Pariat et al, 1997;Zhang et al, 1997), was demonstrated in MCF10 cells at the concentrations/incubation times used of the calpain inhibitors calpastatin peptide and PD150606 (Figure 4b). …”
Section: Brca1 Protein Accumulated After Alln Has An Increased Half-lifementioning
confidence: 76%
“…WT p53 is degraded through proteasomes (Ciechanover, 1994) and by calpain Zhang et al, 1997;Gonen et al, 1997) and inhibition of proteasomes leads to accumulation of wt p53 (Maki et al, 1996;Blagosklonny et al, 1996b;Dietrich et al, 1996). Similarly, the levels of wt p53, can be increased by DNA-damaging agents (Maltzman and Czyzyk, 1984 ;Kastan et al, 1991Kastan et al, , 1992Fritsche et al, 1993), and some other stimuli.…”
mentioning
confidence: 99%